Development of “Berbudi” (Learning Indonesian Culture) Interactive Learning Media Using Articulate Storyline in the IPAS Subject for Fourth-Grade Students at SD Negeri 2 Puru, Trenggalek Regency - Anis Ekowati; Ria Fajrin Rizqy Ana; Imam Sukwatus Suja'i (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The rapid development of digital technology in the globalization era demands innovation in learning resources that can present material concretely; however, in reality, IPAS learning on cultural diversity in schools is still dominated by lecture methods that tend to be abstract and less engaging for students. This study aims to: (1) describe the development process of